Latino images in film : stereotypes, subversion, resistance - Berg, Charles Ramirez, 1947- (Texas film and media studies series, 2002)
The bandido, the harlot, the male buffoon, the female clown, the Latin lover, and the dark lady--these have been the defining, and demeaning, images of Latinos in U.S. cinema for more than a century. In this book, Charles Ramírez Berg develops an innovative theory of stereotyping that accounts for the persistence of such images in U.S. popular culture. He also explores how Latino actors and filmmakers have actively subverted and resisted such stereotyping. In the first part of the book, Berg sets forth his theory of stereotyping, defines the classic stereotypes, and investigates how actors such as Raúl Julia, Rosie Pérez, José Ferrer, Lupe Vélez, and Gilbert Roland have subverted stereotypical roles. In the second part, he analyzes Hollywood's portrayal of Latinos in three genres: social problem films, John Ford westerns, and science fiction films. In the concluding section, Berg looks at Latino self-representation and anti-stereotyping in Mexican American border documentaries and in the feature films of Robert Rodríguez. He also presents an exclusive interview in which Rodríguez talks about his entire career, from Bedhead to Spy Kids, and comments on the role of a Latino filmmaker in Hollywood and how he tries to subvert the system.